The Effect of Perceived Ease of Use, Perceived Enjoyment, Perceived Cohesion, Social Norm and Customer Preference to Customer Loyalty Online Game Community First Person Shooter in Surabaya - Naradipa, Citragosa (KnE Social Sciences, 2020)
Purpose of this study was to determine the effect of perceived ease of use, perceived enjoyment, perceived cohesion, social norm and customer preference on customer loyalty online game community First Person Shooter (FPS) in Surabaya. This research using Structural Equation Modeling (SEM) with Lisrel 8.70 software. Sampling techniques used in this research are non probability sampling with this type of convenience sampling. Data collected directly from respondents who meet the specified characteristics of the population by distributing questionnaires. The samples used in this study was 160 respondents. The results of this study showed the influence of customer preference on customer loyalty, perceived ease of use on perceived enjoyment, perceived enjoyment on customer preference, perceived cohession on customer preference, perceived enjoyment on customer preference, social norm on customer loyalty online game community First Person Shooter (FPS) in Surabaya. While, perceived ease of use on customer preference, perceived enjoyment on customer loyalty online game community First Person Shooter (FPS) in Surabaya rejected. Keywords: Perceived Of Use, Perceived Enjoyment, Perceived Cohesion, Social Norm, Customer Preference, Customer Loyalty